Peripapillary Choroidal Neovascular Membrane Secondary to Sarcoidosis-Related Panuveitis: Treatment with Aflibercept and Ranibizumab with a 50-month Follow-Up - Artemis Matsou (Case Reports in Ophthalmology, 2021)
A case of peripapillary choroidal neovascular membrane (PCNM) secondary to sarcoidosis-related panuveitis successfully treated with anti-vascular endothelial growth factor (anti-VEGF) agents and systemic immunomodulatory therapy is reported. Diagnosis and follow-up were based on fundoscopic, optical coherence tomography as well as fluorescein angiography findings. A 45-year-old female patient presented with sudden onset bilateral blurring of vision. Fundoscopy revealed bilateral granulomatous panuveitis with solitary peripheral granuloma in the right eye and PCNM in the left eye. Diagnostic work-up including conjunctival biopsy confirmed the diagnosis of sarcoidosis. Topical and systemic corticosteroids controlled the inflammation. Within 4 weeks, PCNM showed rapid enlargement (best-corrected visual acuity [BCVA]: 6/60) with foveal involvement. Monthly intravitreal aflibercept injections and systemic methotrexate were administered. After 5 aflibercept injections, anatomical and functional improvement was noted (BCVA: 6/6). Due to aflibercept unavailability, further treatment included ranibizumab injections. During a 50-month follow-up period, every anti-VEGF injection was followed by total NV regression and 6/6 BCVA. Both aflibercept and ranibizumab appear to be effective in the treatment of PCNM secondary to sarcoidosis.